Intertekstualitas dalam Novel “Hati Suhita” Karya Khilma Anis - Ixsir Eliya; Ulfah Mey Lida; Veni Nurpadillah; Anita Kurnia Rachman; Rahmad Nuthihar (Badan Pengembangan dan Pembinaan Bahasa, 2024)
This study describes the intertextual relationship between the characters and plot of the novel